Bibliometric Analysis on Era 4.0: Main Highlights for the Agricultural Sector - Martinho, Vítor (2022)
New realities created through contexts associated with climate change have brought about additional worldwide challenges specifically to deal with the needs of an increasing population without compromising any sustainable Development Goals. A better organisation of the agri-food chains through more efficient practices are the objectives for both national institutions and international organisations. The frameworks related to Era 4.0, namely those interlinked with Agriculture 4.0, Food 4.0 and Industry 4.0, may provide relevant contributions to these challenges. From this perspective, the intention of this study is to highlight bibliometric insights from the literature concerning Era 4.0 and agriculture. For that reason, a bibliometric analysis was carried out, considering bibliographic data, with documents obtained from the Web of Science and Scopus for the topics “agricultur* 4.0”, “agricultur* and food 4.0” and “agricultur* and industry 4.0”. The results obtained show that there are leading authors, organisations and countries in these subjects that may be considered as benchmarks for other researchers worldwide.